A Systematic Review on the Efficacy and Safety of the Combination of Elexacaftor, Tezacaftor, and Ivacaftor in Patients with Cystic Fibrosis (East West Medical College Journal, 2025)
Introduction: Elexacaftor/Tezacaftor/Ivacaftor is a new combination of Cystic fibrosis transmembrane conductance regulator (CFTR)-based treatment, which modulates and corrects the CFTR protein. Several recent clinical trials reported promising responses to this combination of treatment among cystic fibrosis patients.Aim: This systematic review aims to evaluate the safety and efficacy of the combination of Elexacaftor, Tezacaftor, Ivacaftor in cystic fibrosis patients.Methods: Three healthcare-related databases were searched, namely, PubMed, Cochrane registry for clinical trials, cumulative index of nursing and allied healthcare literature (CINAHL). Search was conducted based on the relevant keywords and medical subject headings (MeSH). These search results were searched for duplications and removed if any, thereafter, these studies underwent superficial (based on title and abstract) screening and thorough screening (based on the full-text study) according to the inclusion and exclusion criteria. Finally, six clinical trials were selected from which the efficacy and safety data were collected. Furthermore, risk of bias data was collected based on the JADAD scale.Results: Six clinical trials were included with total with 994 cystic fibrosis patients, 542 were recipients of combination of Elexacaftor, Tezacaftor and Ivacaftor and 452 cystic fibrosis patients received placebo in the control arm, including one single-arm study with 66 patients, who received only triple combination therapy. Three studies included F508del homozygous while three studies included heterozygous patients. Four clinical trials were conducted among adult (>20 years) and two were conducted among child patients. All six trials reported higher ppFEV1 among the triple combination therapy recipients ranging from 9.5% to 13.6%. Furthermore, reduced sweat chloride concentration was reported by 5 out 6 clinical trials, ranging from -33.3 to -60.9 point. Moreover, health-related quality of life improvement was reported by higher CFQ-R RD (cystic fibrosis questionnaire-revised respiratory domain) ranging from 5.9 to 21.9 points. Regarding safety, better nutritional status was reported with BMI change ranging from 0.58 to 1.24, however, there were no difference in pulmonary exacerbations and adverse effect in these two arms. Pulmonary exacerbations ranged from 1.7% to 65% while adverse effects ranged from 28.9% to 93.4%. The clinical trials with child patients reported similar to ppFEV1, higher reductions in sweat chloride concentration, lower CFQ-R RD values, and much higher rates of adverse effects compared adult cystic fibrosis patients.Conclusion: This systematic review showed that combination of Elexacaftor, Tezacaftor, and Ivacaftor is more efficacious than placebo in cystic fibrosis patients. This review also reported that there was no difference in adverse effect or pulmonary exacerbations between these two arms, however, there is different trend in efficacy and safety of child and adult cystic fibrosis patients.EWMCJ Vol. 13, No. 1, January 2025: 4-16